Socio-economic feasibility of potato cultivation in Andhra Pradesh, India - Rana, R.K.; Arya, S.; Kadian, M.S.; Singh, B.P.; Quiróz, R.; Monneveux, P. (Springer, 2016)
The potato processing industry has developed quickly during the past decade in India, and the demand for processing grade potato tubers has increased accordingly. As a consequence, potato market prices have dramatically risen, particularly in the southern states, where production is still limited. The potential for developing the production in these non-traditional areas has been demonstrated. Agronomical and socio-economic constraints need, however, to be better identified and addressed. The International Potato Centre (CIP) and the ICAR-Central Potato Research Institute (ICAR-CPRI), Shimla, have realized a joint survey to analyse the socio-economic factors determining the feasibility and profitability of potato cultivation in the Ananthapuramu and Kurnool districts of Andhra Pradesh State. Respondents established a list of climatic, natural, inputs marketing, technical knowhow and policy support constraints and identified high temperatures, availability and access to irrigation water, price and quality of seeds and costs of inputs as the main potential limiting factors of potato yield. A profitability analysis of potato cultivation under different price and yield scenarios, comparing different crops cultivated by the respondents, indicated that potato was an attractive crop in both districts. A sensitivity analysis, however, revealed a low profitability resilience under the unexpectedly worse productivity conditions in the Kurnool district, where the estimated yield level is already significantly lower than in the Ananthapuramu district due to heat stress. The study consequently recommends introduction of potato in the Ananthapuramu district along with a suggested action plan to address the main production constraints and ensure profitability to the farmers.